Protocol for the development of versions of the Montreal Cognitive Assessment (MoCA) for people with hearing or vision impairment. Issue 3 (30th March 2019) - Dawes, Piers; Pye, Annie; Reeves, David; Yeung, Wai Kent; Sheikh, Saima; Thodi, Chyrssoula; Charalambous, Anna Pavlina; Gallant, Kathleen; Nasreddine, Ziad; Leroi, Iracema
Abstract : Introduction: Hearing and vision impairments are highly prevalent among older adults and impact commonly used cognitive assessment tools for the identification of dementia. Adaptations of such tests for people with hearing or vision impairment have not been adequately validated among populations with such sensory impairment. Methods and analysis: We will develop two versions of the Montreal Cognitive Assessment (MoCA) for people with acquired hearing impairment (MoCA-H) or vision impairment (MoCA-V). The MoCA-H and MoCA-V will exclude the existing MoCA items that are presented in spoken or visual format, respectively, and include new suitably adapted items. Participants (n=792) with combinations of hearing, vision and cognitive impairment will complete standard or adapted versions of the MoCA across three language sites (English, French and Greek). Development of the MoCA-H and the MoCA-V will be based on analysis of adapted and standard MoCA items following model-based development to select the combination of items for the MoCA-H and MoCA-V that provide optimal sensitivity and specificity for detection of dementia. Ethics and dissemination: The study has received ethical approval from respective centres in the UK, France, Greece and Cyprus. The results of the study will be disseminated through peer-reviewed publication, conference presentations, the study website (https://www.sense-cog.eu/ ), the SENSE-Cog Twitter account (@sense_cog) and the MoCA test website (https://www.mocatest.org/ ). The main outputs of the study will be versions of the MoCA that are appropriate for use with adults with acquired hearing or vision impairment and will contribute significantly to the clinical care of older people.